Modification of Digital Oil Pressure Measurement Equipment using Bluetooth Technology - Rasma Rasma; Thomas Junaedi; Hendro Purwono; Riki Effendi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2019)
PT United Tractors Tbk Jakarta workshop held a lot of Machine Inspection Programs for Komatsu units. During the implementation of the Machine Inspection Program (PPM) the machine inspection program is one part of the maintenance that is carried out periodically to obtain accurate data on the condition of the equipment at the time by carrying out checks and adjustments using measurement methods and diagnostic instruments The use of a pressure gauge is still using manual and has a measurement distance that is still limited, if workers or mechanics are not equipped with sufficient knowledge then the pressure gauge will have the potential for error in use and the selection of a pressure gauge is not appropriate to the pressure gauge directly connected to the hydraulic pressure through the hose then the work process ppm is not enough 1 manpower. Therefore it is necessary to modify a digital pressure gauge that has a wide range of scales, in addition a wireless connection is needed to enable the operation of the unit and measurements are made 1 manpower and Bluetooth is one of the right choices in addition to the reach can be met in an application not too difficult so that readings measurement results can be connected directly via mobile.